Attitudes towards English: a case study of form one Malay students / Ghazlina Mohd Ghazali - Mohd Ghazali, Ghazlina (2006)
The purpose of this study was to investigate the attitudes of Form One Malay students towards English. The study was carried out following the grave concern over the lack of English competency particularly among Malay students both at school as well as at tertiary level. The sample in this study was selected from among Form One students in order to find out if the switch in the medium of instructions from Malay language to English for Science and Maths had any influence on their attitude towards English. The qualitative method was used which was a case study. Interviews were carried out on eight subjects who fulfilled the criterion for high and low proficiency, with equal representations of both genders. Findings from this study suggest that there are some differences in attitude between the high and low proficiency students. However, it is found that the high proficiency students do not always have positive attitudes towards English, and the low proficiency students are not totally negative in their attitudes. The negative attitude towards Malays who speak English which was found among students at tertiary level (Parilah Mohd Shah, 1999) was not found to be dominant among the students in this study. The switch in the medium of instructions for Science and Maths increased the importance of learning English among the low proficiency students, but made no difference on the high proficiency students. This study also found very little difference in attitude between genders.